Art history contemporary perspectives on method - Arnold, Dana (Art history special issues, 2010)
Examines the various patterns and approaches to the discipline of art history exhibited across the scholarship of all periods over the last 30 years, resulting in a cross section of art history in all its complexities and a timely survey of its historiography. This collection of newly commissioned essays by a leading group of international scholars examines the various patterns and approaches to the discipline of art history over the last 30 years. The book takes a trans-disciplinary approach to the history of Art History, presenting a cross section of the field in all its complexities.